You are on page 1of 6

# INTEGRALES

(PUEDE SUMARSE UNA CONSTANTE ARBITRARIA A CADA INTEGRAL)
1.
_
x
n
dx =
1
n + 1
x
n+1
(n = −1)
2.
_
1
x
dx = log | x |
3.
_
e
x
dx = e
x
4.
_
a
x
dx =
a
x
log a
5.
_
sen x dx = −cos x
6.
_
cos x dx = sen x
7.
_
tan x dx = −log |cos x|
8.
_
cot x dx = log |sen x|
9.
_
sec x dx = log |sec x + tan x| = log
¸
¸
¸
¸
tan
_
1
2
x +
1
4
π

¸
¸
¸
10.
_
csc x dx = log |csc x −cot x| = log
¸
¸
¸
¸
tan
1
2
x
¸
¸
¸
¸
11.
_
arcsen
x
a
dx = x arcsen
x
a
+

a
2
−x
2
(a > 0)
12.
_
arccos
x
a
dx = x arccos
x
a

a
2
−x
2
(a > 0)
13.
_
arctan
x
a
dx = x arctan
x
a

a
2
log
_
a
2
+ x
2
_
(a > 0)
14.
_
sen
2
mx dx =
1
2m
(mx −sen mx cos mx)
15.
_
cos
2
mx dx =
1
2m
(mx + sen mxcos mx)
1
16.
_
sec
2
x dx = tan x
17.
_
csc
2
x dx = −cot x
18.
_
sen
n
x dx = −
sen
n−1
x cos x
n
+
n −1
n
_
sen
n−2
x dx
19.
_
cos
n
x dx =
cos
n−1
x sen x
n
+
n −1
n
_
cos
n−2
x dx
20.
_
tan
n
x dx =
tan
n−1
x
n −1

_
tan
n−2
x dx (n = 1)
21.
_
cot
n
x dx =
cot
n−1
x
n −1

_
cot
n−2
x dx (n = 1)
22.
_
sec
n
x dx =
tan x sec
n−2
x
n −1
+
n −2
n −1
_
sec
n−2
x dx (n = 1)
23.
_
csc
n
x dx =
cot x csc
n−1
x
n −2
+
n −2
n −1
_
csc
n−2
x dx (n = 1)
24.
_
senh x dx = cosh x
25.
_
cosh x dx = senh x
26.
_
tanh x dx = log |cosh x|
27.
_
coth x dx = log |sen hx|
28.
_
sech x dx = arctan (senh x)
29.
_
csch x dx = log
¸
¸
¸tanh
x
2
¸
¸
¸ = −
1
2
log
cosh x + 1
cosh x −1
30.
_
senh
2
x dx =
1
4
senh 2x −
1
2
x
31.
_
cosh
2
x dx =
1
4
senh 2x +
1
2
x
32.
_
sech
2
x dx = tanh x
2
33.
_
senh
−1
x
a
dx = xsenh
−1
x
a

x
2
−a
2
(a > 0)
34.
_
cosh
−1
x
a
dx =
_
xcosh
−1 x
a

x
2
−a
2
_
cosh
−1
_
x
a
_
> 0, a > 0
¸
xcosh
−1 x
a
+

x
2
−a
2
_
cosh
−1
_
x
a
_
< 0, a > 0
¸
35.
_
tanh
−1
x
a
dx = xtanh
−1
x
a
+
a
2
log
¸
¸
a
2
−x
2
¸
¸
36.
_
1

a
2
+x
2
dx = log
_
x +

a
2
+ x
2
_
= sen h
−1
x
a
(a > 0)
37.
_
1
a
2
+x
2
dx =
1
2
arctan
x
a
(a > 0)
38.
_

a
2
−x
2
dx =
x
2

a
2
−x
2
+
a
2
2
arcsen
x
a
(a > 0)
39.
_
_
a
2
−x
2
_3
2
dx =
x
8
_
5a
2
−2x
2
_ √
a
2
−x
2
+
3a
4
8
arcsen
x
a
(a > 0)
40.
_
1

a
2
−x
2
dx = arcsen
x
a
(a > 0)
41.
_
1
a
2
−x
2
dx =
1
2a
log
¸
¸
¸
¸
a + x
a −x
¸
¸
¸
¸
42.
_
1
(a
2
−x
2
)
3
2
dx =
x
a
2

a
2
−x
2
43.
_

x
2
±a
2
dx =
x
2

x
2
±a
2
±
a
2
2
log
¸
¸
¸x +

x
2
±a
2
¸
¸
¸
44.
_
1

x
2
−a
2
dx = log
¸
¸
¸x +

x
2
−a
2
¸
¸
¸ = cosh
−1
x
a
(a > 0)
45.
_
1
x(a +bx)
dx =
1
a
log
¸
¸
¸
¸
x
a + bx
¸
¸
¸
¸
46.
_
x

a + bx dx =
2 (3bx −2a) (a + bx)
3
2
15b
2
47.
_

a + bx
x
dx = 2

a + bx + a
_
1
x

a + bx
dx
48.
_
x

a + bx
dx =
2 (bx −2a)

a + bx
3b
2
3
49.
_
1
x

a +bx
dx =
_
_
_
1

a
log
¸
¸
¸

a+bx−

a

a+bx+

a
¸
¸
¸ (a > 0)
2

−a
arctan
_
a+bx
−a
(a > 0)
50.
_

a
2
−x
2
x
dx =

a
2
−x
2
−a log
¸
¸
¸
¸
a +

a
2
−x
2
x
¸
¸
¸
¸
51.
_
x

a
2
−x
2
dx = −
1
3
_
a
2
−x
2
_3
2
52.
_
x
2

a
2
−x
2
dx =
x
8
_
2x
2
−a
2
_ √
a
2
−x
2
+
a
4
8
arcsen
x
a
(a > 0)
53.
_
1
x

a
2
−x
2
dx = −
1
a
log
¸
¸
¸
¸
a +

a
2
−x
2
x
¸
¸
¸
¸
54.
_
x

a
2
−x
2
dx = −

a
2
−x
2
55.
_
x
2

a
2
−x
2
dx = −
x
2

a
2
−x
2
+
a
2
2
arcsen
x
a
(a > 0)
56.
_

x
2
+ a
2
x
dx =

x
2
+ a
2
−a log
¸
¸
¸
¸
¸
a +

x
2
+ a
2
x
¸
¸
¸
¸
¸
57.
_

x
2
−a
2
x
dx =

x
2
−a
2
−a arccos
a
| x |
=

x
2
−a
2
−arcsec
_
x
a
_
(a > 0)
58.
_
x

x
2
±a
2
dx =
1
3
_
x
2
±a
2
_3
2
59.
_
1
x

x
2
+ a
2
dx =
1
a
log
¸
¸
¸
¸
x
a +

x
2
+ a
2
¸
¸
¸
¸
60.
_
1
x

x
2
−a
2
dx =
1
a
arccos
a
| x |
(a > 0)
61.
_
1
x
2

x
2
±a
2
dx = ±

x
2
±a
2
a
2
x
62.
_
x

x
2
±a
2
dx =

x
2
±a
2
63.
_
1
ax
2
+bx +c
dx =
_
1

b
2
−4ac
log
¸
¸
¸
2ax+b−

b
2
−4ac
2ax+b+

b
2
−4ac
¸
¸
¸ (b
2
> 4ac)
2

4ac−b
2
arctan
2ax+b

4ac−b
2
(b
2
< 4ac)
4
64.
_
x
ax
2
+bx +c
dx =
1
2a
log
¸
¸
ax
2
+ bx + c
¸
¸

b
2a
_
1
ax
2
+ bx + c
dx
65.
_
1

ax
2
+bx +c
dx =
_
1

a
log |2ax + b + 2

a

ax
2
+ bx + c| (a > 0)
1

−a
arcsen
−2ax−b

b
2
−4ac
(a < 0)
66.
_

ax
2
+ bx + c dx =
2ax +b
4a

ax
2
+ bx + c +
4ac −b
2
8a
_
1

ax
2
+ b + c
dx
67.
_
x

ax
2
+bx +c
dx =

ax
2
+bx +c
a

b
2a
_
1

ax
2
+ bx + c
dx
68.
_
1
x

ax
2
+bx +c
dx =
_
−1

c
log
¸
¸
¸
2

c

ax
2
+bx+c+bx+2c
x
¸
¸
¸ (c > 0)
1

−c
arcsen
bx+2c
|x|

b
2
−4ac
(c < 0)
69.
_
x
3

x
2
+ a
2
dx =
_
1
5
x
2

2
15
a
2
_
_
(a
2
+ x
2
)
3
70.
_

x
2
±a
2
x
4
dx =

_
(x
2
±a
2
)
3
3a
2
x
3
71.
_
sen ax sen bx dx =
sen(a −b)x
2(a −b)

sen(a + b)x
2(a + b)
_
a
2
= b
2
_
72.
_
sen ax cos bx dx =
cos(a −b)x
2(a −b)

cos(a + b)x
2(a + b)
_
a
2
= b
2
_
73.
_
cos ax cos bx dx =
sen(a −b)x
2(a −b)

sen(a + b)x
2(a + b)
_
a
2
= b
2
_
74.
_
sec x tan x dx = sec x
75.
_
csc x cot x dx = −csc x
76.
_
cos
m
x sen
n
x dx =
cos
m−1
x sen
n−1
+x
m + n
+
m−1
m + n
_
cos
m−2
x sen
n
x dx =
= −
sen
n−1
x cos
m+1
x
m +n
+
n −1
m + n
_
cos
m
x sen
n−2
x dx
77.
_
x
n
sen ax dx = −
1
a
x
n
cos ax +
n
a
_
x
n−1
cos ax dx
78.
_
x
n
cos ax dx =
1
a
x
n
sen ax −
n
a
_
x
n−1
sen ax dx
5
79.
_
x
n
e
ax
dx =
x
n
e
ax
a

n
a
_
x
n−1
e
ax
dx
80.
_
x
n
log(ax) dx = x
n+1
_
log ax
n + 1

1
(n + 1)
2
_
81.
_
x
n
(log ax)
m
dx =
x
n+1
n + 1
(log ax)
m

m
n + 1
_
x
n
(log ax)
m−1
dx
82.
_
e
ax
sen bx dx =
e
ax
(a sen bx −b cos bx)
a
2
+ b
2
83.
_
e
ax
cos bx dx =
e
ax
(b sen bx + a cos bx)
a
2
+ b
2
84.
_
sech x tanh x dx = −sech x
85.
_
csch x coth x dx = −csch x
6